Virtual Reality design-build-test games with physics simulation: opportunities for researching design cognition. Issue 3 (3rd July 2021) - Neroni, Maria Adriana; Oti, Alfred; Crilly, Nathan
ABSTRACT: Increasing the range of methods available for researching design cognition provides new opportunities for studying the phenomena of interest. Here we propose an approach for observing design activities, using Virtual Reality (VR) design-build-test games with built-in physics simulation. To illustrate this, we report on two exploratory design workshops where two groups of participants worked to solve a technical design problem using such a platform. Participants were asked to sketch ideas to solve the problem, and then to design, test and iterate some of their developed design concepts in a VR game. Researchers were able to obtain continuous and multifaceted recordings of participants' behavior during the various design activities. This included on-screen design activities, verbal utterances, physical gestures, digital models of design outputs, and records of the test outcomes. Our experiences with the workshops are discussed with respect to the opportunities that similar VR game platforms offer for design cognition research, both in general and specifically in terms of ideation, prototyping, problem reframing, intrinsic motivation and demonstrated vulnerability. VR game platforms not only offer a valuable addition to existing research options, but additionally offer a basis for developing training interventions in design education and practice.